PENERAPAN LABORATORIUM ALAM DALAM RANGKA PENGEMBANGAN KARAKTER SISWA DI SEKOLAH LUAR BIASA (SLB) - ., soripada; abidin, jainal; nasution, eni sumanti; mandopa, andi saputra (Jurnal Nauli, 2021)
The natural laboratory is an introduction to practical tools that are directly obtained in the surrounding area. The application of natural laboratories in external schools is very useful because in extraordinary schools we can meet students who have physical deficiencies. Extraordinary schools in Hutaimbaru have shortcomings including the deaf, mentally retarded where students here can't hear, so that in this service activity direct practicum is used through the tools found in the place, so that the students understand better and the student's character is better. sharpened. This is because students know that with this natural laboratory, students indirectly know that the learning obtained at school can be obtained through students' direct experience.